Pengaruh Guncangan Harga Batubara Dan Fluktuasi Nilai Tukar Terhadap Imbal Hasil Pasar Saham Pada Sektor Energi - Rizki, Anita; Andini; Gunawan, Didik; Cahyadi, Lukieto (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study examines the effect of coal price changes and exchange rate dynamics on stock returns in Indonesia's energy sector. Using secondary data covering the time span from January 2022 to December 2024 and applying the Autoregressive Distributed Lag (ARDL) approach, the study finds that coal prices have a noticeable impact on stock returns in the short period, but do not show a meaningful influence in the longer time horizon. In contrast, exchange rate movements are shown to have important effects in both short and long horizons. The results provide a new perspective for investors in strategizing in the energy sector, highlighting the need to consider coal prices for short-term decisions and exchange rates for long-term planning.